A Comparison of Fish Oil Sources for Parenteral Lipid Emulsions in a Murine Model. (February 2017) - Fell, Gillian L.; Cho, Bennet S.; Pan, Amy; Nose, Vania; Anez-Bustillos, Lorenzo; Dao, Duy T.; Baker, Meredith A.; Nandivada, Prathima; Gura, Kathleen M.; Puder, Mark
Background: Fat emulsions are important components of parenteral nutrition (PN). Fish oil (FO) emulsions reverse cholestasis in PN-associated liver disease. There are 2 FO monographs. One is "FO; rich in omega-3 fatty acids" (NFO). The other, "omega-3 acids, " (PFO), is enriched in omega-3 fatty acids, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The purpose of this study is to compare the effects of 20% NFO and PFO emulsions produced in the laboratory in a murine model. Methods: Emulsions were compounded containing different oils: soybean oil (SO), NFO, and two PFOs differing in percentage of fatty acids as triglycerides (PFO66 and PFO90). Chow-fed mice received saline, one of the above emulsions, or a commercial FO (OM) intravenously (2.4 g/kg/day) for 19 days. On day 19, animals were euthanized. Livers, spleens, and lungs were procured for histologic analysis. Results: OM, SO, NFO, and PFO90 were well-tolerated clinically. PFO66 resulted in tachypnea and lethargy for 1 minute following injections. At euthanasia, PFO66 and PFO90 groups had organomegaly. Histologically, these groups had splenic and hepatic fat-laden macrophages, and lungs had scattered fat deposits. Other groups had normal organs. Conclusions: PFO emulsions present an attractive possibility for improving inflammation in PN-dependent patients by concentrating anti-inflammatory EPA and DHA. However, 20% PFO emulsions were poorly tolerated and precipitated adverse end organ sequelae, suggesting that they may not be safe. Development of novel manufacturing methods may achieve safe 20% PFO parenteral emulsions, but by established formulation methods, these emulsions were clinically suboptimal despite meeting pharmacopeial standards.